2022
DOI: 10.3389/fgene.2022.818727
|View full text |Cite
|
Sign up to set email alerts
|

An Epigenetic Alphabet of Crop Adaptation to Climate Change

Abstract: Crop adaptation to climate change is in a part attributed to epigenetic mechanisms which are related to response to abiotic and biotic stresses. Although recent studies increased our knowledge on the nature of these mechanisms, epigenetics remains under-investigated and still poorly understood in many, especially non-model, plants, Epigenetic modifications are traditionally divided into two main groups, DNA methylation and histone modifications that lead to chromatin remodeling and the regulation of genome fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 221 publications
(236 reference statements)
0
18
0
Order By: Relevance
“…In most cases, a high methylation level at the promoter in all sequence contexts is associated with a reduced gene expression [ 35 ], although in a few cases the reverse situation was demonstrated, as for example for the Arabidopsis ROS1 gene [ 36 , 37 ]. Moreover, transcriptional regulation through DNA methylation has been shown to play important roles during plant development and in response to environmental changes [ 38 , 39 , 40 , 41 ]. Interestingly, the genes whose expression regulation involves DNA methylation include a number of genes related to plant metabolism and in particular to plant secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, a high methylation level at the promoter in all sequence contexts is associated with a reduced gene expression [ 35 ], although in a few cases the reverse situation was demonstrated, as for example for the Arabidopsis ROS1 gene [ 36 , 37 ]. Moreover, transcriptional regulation through DNA methylation has been shown to play important roles during plant development and in response to environmental changes [ 38 , 39 , 40 , 41 ]. Interestingly, the genes whose expression regulation involves DNA methylation include a number of genes related to plant metabolism and in particular to plant secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, phenotypic plasticity patterns do not always follow the principles of Mendelian genetics ( Foust et al, 2016 ; Yi and Goodisman, 2021 ; Guarino et al, 2022 ) and instead are shown to be supported largely by epigenetic mechanisms that generally originate as combinatorial effects of the interactions of genotypes with the environment (Genotype x Environment, abbreviated as GxE) ( Peltier et al, 2018 ). The classic example showing that epigenetic mechanisms generate phenotypic variability came from studies in Linaria vulgaris ( Cubas et al, 1999 ).…”
Section: Epigenetic Variability Generates Phenotypic Plasticity Leadi...mentioning
confidence: 99%
“…In recent decades, emerging epigenetic processes have been highlighted as promising mechanisms to facilitate the generation of the first tier of rapid phenotypic diversity required to improve the fitness and adaptive responses in the natural populations of plants ( Bräutigam et al, 2013 ; Amaral et al, 2020 ; Ashe et al, 2021 ). A survey of published literature shows that a large number of research investigations wherein the epigenetic route has been shown to deploy rapid phenotypic plasticity for adaptation and evolution have come from studies in model plant and crop species ( Ding et al, 2018 ; Guarino et al, 2022 ; Varotto et al, 2022 ) which is primarily due to the availability of large genomic resources accumulated in this group of plants. The advancement in sequencing technologies and their cost effectiveness, has lately facilitated the availability of genomic resources in natural populations of non-model species as well.…”
Section: Epigenetic Variability Generates Phenotypic Plasticity Leadi...mentioning
confidence: 99%
See 2 more Smart Citations